Satb2 determines miRNA expression and long-term memory in the adult central nervous system - Clemens Jaitner; Chethan Reddy; Andreas Abentung; Nigel Whittle; Dietmar Rieder; Andrea Delekate; Martin Korte; Gaurav Jain; Andre Fischer; Farahnaz Sananbenesi; Isabella Cera; Nicolas Singewald; et al. (eLife, 2016)
SATB2 is a risk locus for schizophrenia and encodes a DNA-binding protein that regulates higher-order chromatin configuration. In the adult brain Satb2 is almost exclusively expressed in pyramidal neurons of two brain regions important for memory formation, the cerebral cortex and the CA1-hippocampal field. Here we show that Satb2 is required for key hippocampal functions since deletion of Satb2 from the adult mouse forebrain prevents the stabilization of synaptic long-term potentiation and markedly impairs long-term fear and object discrimination memory. At the molecular level, we find that synaptic activity and BDNF up-regulate Satb2, which itself binds to the promoters of coding and non-coding genes. Satb2 controls the hippocampal levels of a large cohort of miRNAs, many of which are implicated in synaptic plasticity and memory formation. Together, our findings demonstrate that Satb2 is critically involved in long-term plasticity processes in the adult forebrain that underlie the consolidation and stabilization of context-linked memory.